2008
DOI: 10.1021/jp804327k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Electromagnetic Functionalized Nickel/Polypyrrole Core/Shell Composites

Abstract: Microstructured Ni/PPy (PPy: polypyrrole) core/shell composites were prepared from an in situ chemical oxidative polymerization of pyrrole (Py) monomer in the presence of Ni powder, with ammonium persulfate (APS) as oxidant and citric acid (C6H8O7) as dopant. X-ray diffraction and Fourier transform infrared analyses indicate that there is no chemical interaction between Ni powder and protonated PPy. The mass percentages of PPy, calculated from the remanent weight percentages of Ni/PPy composites after thermogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
172
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(182 citation statements)
references
References 31 publications
8
172
0
2
Order By: Relevance
“…8 shows the results for the reflection loss of the specimens as a function of frequency, in which the thickness for the specimens is 2 mm. The microwave absorbing parameter for the specimens is listed in [13] observed that a relatively low electrical resistivity (namely a relatively high conductivity) is not definitely beneficial to enhancing microwave absorption in nickel/PPy composites. Wan et al [31] proposed that the absorbing parameter of the conducting polymers was not directly proportional to the conductivity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…8 shows the results for the reflection loss of the specimens as a function of frequency, in which the thickness for the specimens is 2 mm. The microwave absorbing parameter for the specimens is listed in [13] observed that a relatively low electrical resistivity (namely a relatively high conductivity) is not definitely beneficial to enhancing microwave absorption in nickel/PPy composites. Wan et al [31] proposed that the absorbing parameter of the conducting polymers was not directly proportional to the conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…Han et al synthesized barium ferrite/PPy nanocomposites [12] and nickel/PPy core-shell nanocomposites [13] and found that the nanocomposites have better reflection loss properties than barium ferrite and nickel alone. Liu et al [14] reported the ZnFe 2 O 4 / PPy core-shell nanocomposites exhibit better microwave absorption performance than ZnFe 2 O 4 alone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 In the case of e 0 this is a direct consequence of a higher number of interfaces prompting polarization (Maxwell-Wagner-Sillars effect) associated with the migration and accumulation of charges at the conductive filler/ polymer interfaces. 34 For e 00 , it is due to the reduction of the average distance between adjacent CNTs which, in turn, implies higher dielectric and ohmic losses.…”
Section: Electromagnetic Characterizationmentioning
confidence: 99%
“…[2][3][4] Core/shell-structured nanocapsules, comprising a magnetic nanoparticle core and a dielectric shell of nanometer size, have attracted considerable attention because of their synergetic effects between dielectric and magnetic losses for absorbing EM waves. [1][2][3][4][5][6][7] Among various types of core/shell-structured nanocapsules, nickel/carbon (Ni/C) nanocapsules are regarded as a highpotential candidate due to their simple material type, simple preparation process, interesting dielectric and magnetic properties, good EM impedance match, and high EM absorption properties, etc. 1,2,6 For instance, a Ni/C nanocapsule absorber with 2.0 mm thickness exhibits a large reflection loss (RL) of ∼-32 dB at ∼13 GHz and a wide effective absorption bandwidth (for RL<-10 dB) of ∼4.3 GHz (i.e.,11.2-15.5 GHz).…”
Section: Introductionmentioning
confidence: 99%